2021
DOI: 10.1126/sciadv.abe4497
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell molecular profiling of all three components of the HPA axis reveals adrenal ABCB1 as a regulator of stress adaptation

Abstract: Chronic activation and dysregulation of the neuroendocrine stress response have severe physiological and psychological consequences, including the development of metabolic and stress-related psychiatric disorders. We provide the first unbiased, cell type–specific, molecular characterization of all three components of the hypothalamic-pituitary-adrenal axis, under baseline and chronic stress conditions. Among others, we identified a previously unreported subpopulation of Abcb1b+ cells involved in stress adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 67 publications
1
61
1
2
Order By: Relevance
“…Abcd1 -deficient microglia have been correlated with synaptic loss and axonopathy [65] pointing to an Abcd1 -dysregulated network association with synaptic signaling problems. Abcb1 , another member of the ABC transporters family, has been associated with stress adaptation and potential mediation of stress-related psychiatric disorders phenotypes [66]. These findings highlighted that the exclusive analysis of transcriptomic data at the gene-level does not capture all aspects of the transcriptional response to a stimulus, and the DN analysis can unravel distinct but complementary aspects that can lead to specific molecular pathways identification.…”
Section: Discussionmentioning
confidence: 99%
“…Abcd1 -deficient microglia have been correlated with synaptic loss and axonopathy [65] pointing to an Abcd1 -dysregulated network association with synaptic signaling problems. Abcb1 , another member of the ABC transporters family, has been associated with stress adaptation and potential mediation of stress-related psychiatric disorders phenotypes [66]. These findings highlighted that the exclusive analysis of transcriptomic data at the gene-level does not capture all aspects of the transcriptional response to a stimulus, and the DN analysis can unravel distinct but complementary aspects that can lead to specific molecular pathways identification.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Senp2 -deficiency preferentially affects the zF while being expressed in all cortical areas 49 can be explained by two non-mutually exclusive mechanisms. First, the zG already harbours high levels of nuclear SUMOylation compared to the zF 20 , therefore the expected increase in SUMOylation conjugates consecutive to lowered deconjugase pools will preferentially affect hypoSUMOylated regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with a large body of literature indicating that neuronal dysfunction in the PFC, the central hub of executive functions, contributes importantly to MDD. There are reports from postmortem brain studies from MDD subjects 48, 49 as well as rodent chronic stress models 47, 50, 51 describing the loss of synapses, a decrease in synaptic-related genes, and alterations in mPFC neuronal electrophysiological properties. Similarly, we found that neuronal expression of FEDORA promotes altered expression of synaptic genes along with changes in neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%